Microdistribution of Tin in Newly Synthesized Organotin(IV)-Treated Tropical Wood Cells - I., Jusoh; A., Husaini; A.H.H., Wong (Asian Network for Scientific Information, 2015)
Penetration of wood preservatives into the wood cell is believed to be important to protect the wood from biodegradation especially fungal degradation. preservatives effectiveness depends on the amount of uptake or retention as well as its uniform distribution within the wood cells. Interest on organotin(IV) complexes both mono- and disubstituted organotin(IV) is increasing due to their interesting structural features, biocidal properties and environmentally friendly. The microdistribution of tin-based preservative in tropical woods was examined using Scanning Electron Microscope-Energy Dispersive X-ray (SEM-EDX) analyzer. Bulk specimens of 1% organotin(IV)-treated cubes were used to examine the microdistribution of tin in Alstonia scholaris, Macaranga triloba and Hevea brasiliensis woods. Conventional SEM-EDX was able to detect spatial distribution of tin in wood microstructure. The SEM-EDX distribution maps and linescan analyses showed that the deposition of tin were uneven with respect to cell microstructure in all woods studied with relatively higher tin accumulation in the ray cells and middle lamella than in the fibre cell wall. The results indicated that ray as the penetration pathway of organotin(IV) solution into the wood microstructure capable of penetrating the cell wall.